Evaluation of Work Posture During Bed Bathing Procedures and Its Association with Musculoskeletal Complaints among Nursing Students - Guru Prapti, Ni Ketut; Damayanti, Made Rini (Faculty of Nursing, Universitas Hasanuddin, 2025)
Aims: This study aimed to analyze the working posture of nursing students while bathing patients in bed and to identify the musculoskeletal complaints experienced by nursing students after the intervention. Methods: This was an analytical observational study aimed at observing and analyzing the work posture of respondents while bathing patients in bed as well as identifying musculoskeletal complaints experienced by nursing students after the intervention. The Rapid Entire Body Assessment (REBA) instrument was used to determine whether the nursing students were working beyond safe limits, while the Nordic Body Map (NBM) was used to identify which parts of the body experienced discomfort. The study was conducted in the Nursing Skill Lab at one of the nursing education institutions in Bali, and involved 19 nursing students performing a case scenario related to fulfilling personal hygiene needs through bed bathing. A video of the activity was recorded and converted into images for analysis by measuring the angles of the various body parts. The scores for each body part were entered into the REBA worksheet to determine the final score. Results: The results of the study showed that wiping the nearest hand, stomach, chest, and foot had a REBA score of 7, indicating a moderate risk. In contrast, wiping the furthest hand, back, and feet had REBA scores ranging from 9 to 10, indicating a high risk. The results of the NBM questionnaire revealed that the most commonly reported musculoskeletal disorders were disorders of the back (57.4%), waist (55.4%), and feet (42.3%). Conclusion: Musculoskeletal complaints during education are a significant concern, as nursing programs must prepare students for a lifelong professional career that includes managing the physical demands of clinical practice. Therefore, modifying work procedures based on comprehensive ergonomic principles is essential, as is providing nursing students with a thorough understanding of proper ergonomic work postures.